Kadar Fenolik Dan Flavonoid Total Dalam Ekstrak Metanol Daun Cemba (Acacia rugata (Lam.) Fawc. Rendle) - Dahlia, Andi Amaliah; Amima, Nur Qadri; S, Aulya Rachma Arum; Syarif, Rezki Amriati; Ahmad, Aktsar Roskiana (Jurnal Fitofarmaka Indonesia, 2022)
This study aims to determine and compare the phenolic and flavonoid content of methanol extract in Acacia rugata (Lam.) Fawc. Rendle leaves using UV-Vis spechtrophotometry and TLC-densitometry. The Acacia rugata (Lam.) Fawc. Rendle extracted by using maceration applied sonicator. The quantitative assay measured by spectrophotometer UV-Vis at wavelength 430 nm. The TLCâ€“densitometry performed at wavelength of 254 nm and quercetin was as a standard. The results showed that the phenolic total showed 0.506 gGAE/g extract for spectrophotometer Uv-Vis and 0.879 gGAE/g extract for TLC-Densitometric. The flavonoid content reported 0.44 gQE/g extract and 0.73 gQE/mg extract for spectrophotometer UV-Vis and TLC Densitometric methods, respectively.Â